DFT-Spread OFDM-Based MIMO Joint Communication and Sensing System - Max Schurwanz; Jan Mietzner; Peter Adam Hoeher (IEEE Open Journal of Vehicular Technology)
This paper introduces a joint communication and sensing (JCAS) system design that employs a discrete Fourier transform (DFT)-spread orthogonal frequency-division multiplexing (OFDM) waveform integrated with a multiple-input multiple-output (MIMO) antenna array. This system has been designed with the specific requirements of future remotely piloted or autonomous aircraft systems in urban air mobility (UAM) settings in mind. The objective is to provide high-bandwidth data transmission in conjunction with precise radar sensing, thereby enhancing situational awareness and facilitating efficient spectrum usage. The paper makes a number of significant contributions to the field, including the development of a flexible MIMO DFT-spread OFDM system model and the introduction of a phase compensation term for comprehensive direction-of-arrival estimation. Additionally, the effects of non-linear power amplifiers on system efficacy are analyzed through detailed simulations, providing a rigorous evaluation of the proposed design's practicality and resilience. The numerical analysis establishes a framework for the design of a JCAS system for UAM, taking into account the influence of realistic electronic components and the respective performance requirements for communication and sensing.